1977
DOI: 10.3758/bf03198721
|View full text |Cite
|
Sign up to set email alerts
|

The effect of environment on visual cliff performance in the Mongolian gerbil

Abstract: Depth perception in the Mongolian gerbil was investigated as a function of age and environment. Thirty-two gerbils were raised in either a cliff or flat environment, and half the gerbils in each condition were tested on the visual cliff from 21 to 57 days of age. All gerbils were tested at 60-61 days on a standard visual cliff, a barrier cliff which prevented movement along the centerboard, and a jumping platform. While the gerbils did not display a preference for the shallow side when tested at 21 days, those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1978
1978
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…Future studies are needed to explore whether habitat shapes key behavioural traits (e.g. boldness) in other populations (Bradley & Shea, 1977).…”
Section: 002mentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies are needed to explore whether habitat shapes key behavioural traits (e.g. boldness) in other populations (Bradley & Shea, 1977).…”
Section: 002mentioning
confidence: 99%
“…Precocial species (e.g. goats, chicks) avoid stepping over the edge of a precipice (Gibson & Walk, 1960;Walk & Gibson, 1961;Walk, 1966;Bradley & Shea, 1977). Experimental studies revealed that, in altricial species (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Jirds are an altricial species in which the offspring depend on parental care for several weeks after birth [ 46 ], whereas spiny mice are precocial and their offspring can become independent within a few days postnatally [ 47 ]. Previous studies have revealed differences in depth perception between precocial and altricial species [ 6 , 48 50 ]. Generally, precocial newborns are able to discriminate depth without prior experience [ 48 , 51 ], whereas in altricial species individuals without prior experience have less accurate depth perception [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Species displaying both efficient and poor depth discrimination were found among both the Microtus and Peromyscus genera. Israeli gerbils, the species showing the highest mean proportion of choices to the shallow side, are congeneric with Mongolian gerbils, a species that has been reported deficient in visual cliff performance (Bradley & Shea, 1977;Thiessen et aI., 1968).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the general finding of good depth perception in the visual cliff in most species, some exceptions have been found. For example, Mongolian gerbils appear deficient in depth perception as assessed using this method (Bradley & Shea, 1977;Thiessen, Lindzey, Blum, Tucker, & Friend, 1968). It has been proposed that variations in the development of depth perception may be correlated with the habitat of the species in question (Routtenberg & Glickman, 1964;Yerkes, 19(4).…”
mentioning
confidence: 99%